Veterinary donation: To what extent can the ethical justifications for living human donation be applied to living animal donation? - Ashall, Vanessa (2017)
This thesis develops the scant existing literature which explores the ethical justifications for living animal donation in the veterinary setting and contributes to the considerable research on social and ethical aspects of human living donation. The work argues that whilst some justifications for human living donation are not-transferable, others may be adapted and applied to the veterinary setting. The unique social context of veterinary donation is analysed, using novel empirical analysis to refine and contextualize the ethical arguments made. The research methods entail an innovative comparative ethical analysis and a qualitative empirical study which are integrated using an empirical bioethics approach. The main justificatory arguments for human living donation are identified as informed consent and donor best interest. These arguments stem from a human’s acknowledged rights to bodily integrity and the human medical professional’s duty not to harm their patients. The reduced capacity of animal donors means that donor consent arguments are not directly transferable to the veterinary setting and an animal owner’s informed consent is shown to have reduced moral authority. Whilst animal donors may lack comparable bodily rights, veterinary living donation practices can conflict with a veterinary surgeon’s professional obligations. A comparable justification for living animal donation is argued to exist only when the procedure is in the donor animal’s best interest. An empirical analysis of canine blood donation to a UK animal blood bank develops understanding of the social context of living animal donation. The analysis indicates that animal owners may not always be motivated by the best interest of donor animals; furthermore, consistent themes such as trust, optimism and human-animal comparisons have implications for the quality of a donor owner’s consent. These ethical and empirical findings are used to construct an ethical framework for living animal donation with detailed provisions for owner consent, donor best interest, donor harm and benefit, recipient benefit, fairness and transparency. The ethical framework is used to argue for the development of regulatory approaches to companion animal blood banking and feline renal transplantation in the UK. The work also has wider implications for veterinary ethics, veterinary policy and the social and ethical understanding of human living donation.